GAMBARAN SIKAP DAN PERILAKU TENAGA KESEHATAN DALAM PENGELOLAAN LIMBAH MEDIS DI RSUD ACEH BESAR - Rizarullah Rizarullah; Satria Safirza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: Hospitals as a unit providing health services to the community not only have a positive impact but also the negative impact that medical waste generated by hospitals if not processed according to the procedure will have adverse health and environmental impacts. Research Objectives: To see the description of attitudes and behavior of health personnel in the treatment of medical waste because the problem there is still found mixed medical and non medical waste. Research Method: This research is descriptive research with research designusing cross sectional approach. In this research data collected through questionnaire method to 114 respondents namely health workers at RSUD Aceh Besar by using simple random sampling technique to know the description of attitude and behavior in medical waste processing. Result: Univariate analysis showed that most respondents had good attitude about medical waste treatment at RSUD Aceh Besar that is 73 people (64%) while respondents who have bad attitude counted 41 people (64%). Then most respondents have good behavior in medical waste processing at RSUD Aceh Besar that is 62 people (54,4%) whereas respondents who have bad behavior as much 52 people (45,6%). Most of the respondents stated that the medical waste treatment in RSUD Aceh Besar was good as many as 66 people (57.9%) while the respondents stated that the medical waste treatment in RSUD Aceh Besar was badas much as 52 people (45,6%).Keywords: Attitude, Behavior, Health Worker, Medical Waste Treatment